Psychological and psychoeducational assessment of children and adolescents who are deaf and hard of hearing - Miller, Margery Staman, 1945- (Washington, DC : Gallaudet University Press, 2015)
The obstacles to valid and meaningful assessment of deaf and hard of hearing children and adolescents are great, yet professionals are regularly asked to conduct comprehensive evaluations to determine resource and program eligibility, test modifications in school, classroom and home recommendations, and referrals. In this important new text, the authors define the skills required of the examiners, explain the complex nature of these assessments, and describe ways to intelligently use existing tests. Authors Margery S. Miller, Tania Thomas-Presswood, Kurt Metz, and Jennifer Lukomski bring a wealth of knowledge and experience to this in-depth treatment of topics essential to educators and school psychologists. They cover such critical areas as test construction and measurement; the diversity in American Deaf culture; the role of parents in the assessment process; neuropsychological assessments; nonverbal methods for assessing intelligence; and the need for sign language competency when testing cognitive and language skills. The text concludes with recommendations for the development of valid and reliable tests for all students who are deaf and hard of hearing.
1. Introduction -- 2. Test Construction and Measurement Issues -- 3. Diversity and Cultural Competence -- 4. Family Involvement in the Assessment Process -- 5. Neuropsychological Assessment -- 6. Methods of Determining Nonverbal Intelligence -- 7. Assessing Verbal and Linguistically Based Cognitive and Language Skills With Children Who Are Deaf and Hard of Hearing: Sorting Out the Complexities -- 8. Assessment of Behavior and Social-Emotional Functioning -- 9. Ascertaining Academic Achievement -- 10. Summary and Future Directions.
Includes bibliographical references and index.
Print version record.
English.
WorldCat record variable field(s) change: 650
Keywords: Deaf children -- Psychological testing; Hard of hearing children -- Psychological testing; Deaf students -- Psychological testing; Psychodiagnostics; Children; Psychological tests; Persons With Hearing Impairments; Child; Adolescent; Psychological Tests; Educational Measurement -- methods; Enfants sourds -- Tests psychologiques; Enfants handicapés auditifs -- Tests psychologiques; Psychodiagnostics; Enfants; Tests psychologiques; children (people by age group); EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; EDUCATION / General; Psychological tests; Children; Hearing impaired children -- Psychological testing; Psychodiagnostics